Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/biology11070977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Traditional and Next-Generation Approaches for Uncovering Phytoplasma Diversity, with Discovery of New Groups, Subgroups and Potential Vectors

Abstract: Despite several decades’ effort to detect and identify phytoplasmas (Mollicutes) using PCR and Sanger sequencing focusing on diseased plants, knowledge of phytoplasma biodiversity and vector associations remains highly incomplete. To improve protocols for documenting phytoplasma diversity and ecology, we used DNA extracted from phloem-feeding insects and compared traditional Sanger sequencing with a next-generation sequencing method, Anchored Hybrid Enrichment (AHE) for detecting and characterizing phytoplasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“… Osbornellus auronitens (Provancher, 1889), the type species of the genus, is a Cicadellidae Deltocephalinae distributed in the north-eastern part of the North American continent throughout Canada and the United States ( Beamer 1937 ). Specifically regarding Europe, this species has been recently recorded for Switzerland (Canton Ticino) in 2016 and 2017 ( Trivellone et al 2017 , Trivellone et al 2022 ); therefore, the data presented here constitute the first record of this non-native species for Italy. The discovery of O.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“… Osbornellus auronitens (Provancher, 1889), the type species of the genus, is a Cicadellidae Deltocephalinae distributed in the north-eastern part of the North American continent throughout Canada and the United States ( Beamer 1937 ). Specifically regarding Europe, this species has been recently recorded for Switzerland (Canton Ticino) in 2016 and 2017 ( Trivellone et al 2017 , Trivellone et al 2022 ); therefore, the data presented here constitute the first record of this non-native species for Italy. The discovery of O.…”
Section: Discussionmentioning
confidence: 71%
“…During both recent trapping activities aimed at collecting Coleoptera in Lombardy (NE Italy) and monitoring activities finalising the survey of the invasive Scaphoideus titanus Ball, 1932 and other Cicadellidae of phytosanitary interest in Piedmont (NW Italy), a species of Osbornellus , extraneous to the Italian fauna, was recorded. The species is here identified as the Nearctic Osbornellus auronitens (Provancher, 1889), representing the third record of this species in the Palaearctic (Europe) (see Trivellone et al (2017) , Trivellone et al (2022) ) and the first one in Italy. In addition, the revision of previously unidentified material revealed the species presence in Italy since at least 2015.…”
Section: Introductionmentioning
confidence: 94%
“…Others have found that it is difficult to obtain sequences from older museum specimens using Sanger sequencing (Joyce et al 2021, Nakahama 2021). Museum collection is a wealth of information about the abundance and genetic composition of insect populations, but collection specimens may need to be sequenced using methods that work better with degraded or fragmented DNA (Trivellone et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that screening potential insect vectors is an efficient alternative method for discovering and characterizing host-phytoplasma associations, allowing presence of phytoplasmas to be detected in the environment in the absence of a disease outbreak [17][18][19]. By using existing data from different biorepositories, this promising strategy focuses on the evaluation of the entire suite of potential insect vectors and plant hosts present in a defined macro-area.…”
Section: Introductionmentioning
confidence: 99%